The Problem of Establishing Consent - A critical policy analysis of how the problem of establishing consent and voluntariness has changed in Swedish rape judgements after the consent law. - Fransson,Linnea (2022)
The aim of this study is to analyse and understand how the problem of establishing consent is represented in Swedish rape judgements before and after the consent-based legislation was enacted in 2018. The purpose is to elucidate differences in the court’s assessment of consent, as well as generate an understanding of how the court may maintain and reproduce problematic elements which are stereotyped in the legal assessment. The issue of involuntary sex was discussed and deliberated upon in the last three government bills, and was also raised by politicians and social movements. The study is based on 21 judgements from Scania and Blekinge Court of Appeal from the years 2017 and 2020. This study incorporates how the law has contributed to an updated legal practice, and if it also can contribute to social change. The thesis is situated within the Foucauldian theory on discourses, power of the law and governmentality, and uses Nils Christie’s concept of the ideal victim. The analysis is based on problematization, where the method of analysis is a critical policy analysis. The problem in this study is grounded in establishing consent in Swedish rape trials. The primary findings of the analysis are that the discussion on consent and voluntariness are more consistent after the consent-based rape legislation was enacted in 2018. The representation of the problem is based on historical, legal and political knowledge and practice. Furthermore, the focus on validating the victim’s narrative in relation to consent is more predominant in judgements from after the consent-based legislation was enacted. The legislation has also contributed to more equal judgements and an incorporation of the discourses on voluntariness as well as the defendant’s intent. Finally, the formerly accepted truth of rape and consent has been redefined by the consent-based legislation, and has contributed to a need for new practice and knowledge.
Keywords: Consent; Voluntariness; Rape; Sweden; Critical policy analysis; Judgement; Legal discourse; Problematization